Pengelolaam data dan informasi status gizi balita dan pengambilan keputusan program gizi di puskesmas se-Kabupaten Majene - Shafwan Shafwan; Hari Kusnanto; Anis Fuad (Jurnal Gizi Klinik Indonesia, 2008)
Background: Improved nutritional status is needed throughout the life cycle including children under five. Of age in formulating suitable policies for nutrition improvement program, decision makers require relevant information about nutritional status of the community. The implementation of health information system at District of Majene is not yet optimum. There are some problems such as inaccurate data, inconsistent or unreliable data, delay in data reporting, and processing and presentation of data are rarely made, reporting is done as routine disregarding data quality, there is no feedback from the health office and so on. Decentralization has offered an opportunity for the health center to make its own policy in optimizing nutrition improvement program. However, health centers at District of Majene have never made decisions based on evidence.Objective: The study aimed to get an overview of data and information management of nutritional status of children under five comprising availability, processing, presentation of data, and the decision making of nutrition program at the health centers of District of Majene.Method: This was a descriptive case study with qualitative method. Subjects of the study were nutrition staff of the health centers, head of health centers, and head of nutrition section of district health office with health centers and head of health office as analysis units. Data were obtained through indepth interview, focus group discussion, questionnaire, observation, and documentation.Results: Data and information on nutritional status of children under five years of age were available in all health centers; however format of reporting was unavailable. Data in LB3 accurate, in FIII/gizi and SKDN were inaccurate because there was data manipulation and cadres had limited skills. Data were not valid because there was no signature of head of the health center in the report. Data in FIII/gizi and SKDN reliable, in LB3 not reliable  because there was no coordination among staff. Data in SKDN were completed, in FIII/gizi and LB3 incomplete because some of the forms were blank. Data were not provided timely due to less commited cadres, geographical factors, and lack of pressure from the health office. Data were accessible because staff were active in maintaining records. Data were processed manually and presented in the form of narratives, tables and graphs. Decisions made were socialization, counseling, growth monitoring and comple- mentary breastfeeding distribution monitoring. However, they were not based on data so that reports were only made as routine activities.Conclusion: Data and information on nutritional status of children under five years of age were available at the health centers with quality data in every format of reporting of various kinds. Data and information were processed manually and presented in the form of narratives, tables, and graphs. Decisions made were socialization, counseling, growth monitoring, and complementary breastfeeding distribution monitoring. Decisions made were not based on data available.